Significance of Regulations in Driving Internal Environmental Management among Contractors for GSCM Application - Ming Heng, Yong; Zakiyuddin Ahmad Rashid, Zul; Riazi Mehdi Riazi, Salman (International Journal of Engineering and Technology, 2018)
This paper is aiming to study the significance of Regulations as driver in Internal Environment Management practice as part of GSCM practices. Accordingly, the objectives are to identify the drivers in driving Internal Environmental Management among Contractors for GSCM application and to analyse the significance of Regulations in comparison to other Drivers in driving Internal Environmental Management among Contractors for GSCM application. Quantitative research design approach is employed in this study. The independent variables in this study are the drivers of GSCM implementation in construction sector, while the dependent variable is the level of adoption of Internal Environmental Management for GSCM application in the construction sector. The result shows that Regulations driver is the significant factor for Internal Environmental Management practice. The research is significant in providing all relevant parties insights into the most significant driver in Internal Environmental Management, so that further improvement can be carried out for a successful GSCM application in Malaysia.Â Â